2020
DOI: 10.3390/sym12091522
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb Asymmetries and Ipsilateral Associations of Plantar Flexors and Knee Extensors Rate-of-Force Development Scaling Factor

Abstract: Rate of force/torque development scaling factor (RFD-SF/RTD-SF) was recently introduced as a tool to quantify the neuromuscular quickness, and it could have potential for interlimb asymmetry identification. Moreover, positive relationships in RFD-SF ability among different muscle groups were shown, but not in the lower extremity. The first aim of our study was to use RTD-SF for interlimb asymmetry identification. The second aim was to determine associations between plantar flexors (PF) and knee extensors (KE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Our third aim was to compare differences and associations between k RFD–SF and k RFR–SF in a larger sample. To date, most of the studies have investigated k RFD–SF of different muscle groups ( Bellumori et al, 2013 ; Casartelli et al, 2014 ; Šarabon et al, 2020b ; Smajla et al, 2020 ), while there are only two studies investigating k RFR–SF on a smaller number of participants ( Mathern et al, 2019 ; Šarabon et al, 2020a ). None of these studies have investigated the associations between k RFD–SF and k RFD–SF , or more specifically, associations between the ability for rapid force production and relaxation during different submaximal contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our third aim was to compare differences and associations between k RFD–SF and k RFR–SF in a larger sample. To date, most of the studies have investigated k RFD–SF of different muscle groups ( Bellumori et al, 2013 ; Casartelli et al, 2014 ; Šarabon et al, 2020b ; Smajla et al, 2020 ), while there are only two studies investigating k RFR–SF on a smaller number of participants ( Mathern et al, 2019 ; Šarabon et al, 2020a ). None of these studies have investigated the associations between k RFD–SF and k RFD–SF , or more specifically, associations between the ability for rapid force production and relaxation during different submaximal contractions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the rate force development scaling factor (RFD-SF) to assess rapid force generation has been more frequently performed and reported after the protocol verification by Bellumori et al (2011) . Since then RFD-SF protocol has been used for isometric neuromuscular assessment of different muscle groups ( Casartelli et al, 2014 ; Djordjevic and Uygur, 2017 ), to explore the effects of aging ( Bellumori et al, 2013 ) and different diseases such as osteoarthritis ( Šarabon et al, 2020a ), and in studies exploring lateral asymmetries in different sports ( Boccia et al, 2018 ; Smajla et al, 2020 ). Moreover, some studies have shown that rate of force relaxation scaling factor (RFR-SF) can be assessed using the RFD-SF protocol with the aim to evaluate the ability of quick relaxation of submaximal muscle forces ( Mathern et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…They found lower symmetry values for knee extensors (82.6 ± 9.1%) compared to male basketball players (93.23 ± 5.6%), male tennis players (92.71 ± 5.1%), and male students (93.24 ± 5.2%) in our sample, which could be explained by a more one-sided nature of soccer (kicking with the preferred leg) compared to the sports included in our sample. In the second study, the authors calculated the k RFD–SF of knee extensors in young athletes and reported that 15% of subjects could be classified as asymmetric ( Smajla et al, 2020 ). In the current literature, there is no data about differences in (a)symmetries using the RFD-SF/RFR-SF protocol between different sports groups or genders.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between peak forces and the corresponding RFDs is represented by the slope of these relationships, specifically the slope of the regression line interpolated on the peak force: RFD scatter plot (k RFD–SF ). This measure enables the investigation of inter-limb asymmetries at movement initiation and quickness of force production, which has been investigated only by two studies to date ( Boccia et al, 2018 ; Smajla et al, 2020 ). Smajla et al (2020) showed that leg preference has no effect on k RFD –SF , while Boccia et al (2018) reported that k RFD –SF has been shown as a more sensitive tool for identifying inter-limb asymmetry compared to a classical isokinetic test ( Boccia et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation